The Role of Organizational on improving Quality of Educational Services: An analytical study of the opinions of faculty members in technical colleges at Sulaimanyah Technical University - فرج عارف سعيد, كاظم; أديب كريم, هوزان (The Scientific Journal of Cihan University– Sulaimaniya, 2024)
This study aims to identify the role of organizational flexibility as an independent variable through its dimensions (structural flexibility, operational flexibility, strategic flexibility) in improving the quality of educational service as a dependent variable with its dimensions represented by (quality of curricula, quality of faculty members, student quality, quality of Scientific research), the technical colleges at Suleimani polytechnic University, represented by six colleges, were chosen as a field to apply the practical aspect of the study, and the study problem was identified by asking the main question, which is what is the role of organizational flexibility in improving the quality of educational service? In order to reach the answer, the study included a set of sub-questions to achieve the objectives of the study. Statistical for Social Sciences (SPSS-V.21) A questionnaire form has been prepared that includes (35) phrases. An evaluation of the form was conducted before distributing the questionnaire by a group of arbitrators, and it was distributed within six colleges, and the number of distributed forms was (220) forms were completed. (197) of them were retrieved, and (185) were valid for analysis, and (21) were excluded because they were not fit for analysis. The study reached a set of conclusions, the most important of which is the existence of a correlation and impact relationship between organizational flexibility and the quality of the educational service, with the variation of this relationship at the level of sub-dimensions in the light of the answers of the respondents, which confirms the importance of organizational flexibility in improving the quality of educational service. Based on the conclusions reached by the research, a set of proposals were presented, the most important of which is the necessity of applying the quality of educational service in the researched faculties and adapting its dimensions to their reality and paying attention to curricula and academic courses because they are means for developing basic skills and diversifying educational services to meet diverse needs and develop skills Faculty members to improve their contribution to providing these services in addition to directing the teaching staff towards new research areas.